Application of ligninolytic bacteria to the enhancement of lignocellulose breakdown and methane production from oil palm empty fruit bunches (OPEFB). (February 2022) - Nurika, Irnia; Shabrina, Eka Nur; Azizah, Nurul; Suhartini, Sri; Bugg, Timothy D.H.; Barker, Guy C.
Abstract: Efficient pretreatment of lignocellulosic biomass is needed to reduce associated energy costs. Lignin-degrading bacteria ( Comamonas testosteroni, Agrobacterium sp., Lysinibacillus sphaericus, and Paenibacillus sp.) were tested as potential pre-treatment methods for oil palm empty fruit bunches (OPEFB) to enhance its methane yield during anaerobic digestion (AD). The lignocellulose fractions were analysed for total reducing sugar (TRS), total soluble phenols (TSP), lignin content, weight loss, pH and microscopic analysis carried out both before and after treatment. The methane production was tested using the biochemical methane potential (BMP) test. Bacteria mediated depolymerisation of OPEFB was confirmed through the observation of increased release of TSP and associated lignin breakdown and weight loss of the cultured OPEFB biomass. The highest percentage of lignin breakdown (25.84%) was obtained from OPEFB treated by Lysinibacillus sphaericus, while the highest average specific methane potential (0.042 m 3 /kg VS) was obtained from treatment with Comamonas testosteroni. Graphical abstract: Unlabelled Image Highlights: Bacterial lignin degraders can breakdown lignocellulose and enhance methane production. The treatment with lignin degrading bacteria makes OPEFB viable for use in anerobic digestion. The mechanism of how bacteria breakdown lignin requires further elucidation.